A Versatile One-Pot Strategy for the Synthesis of [1,4]Thiazepino[5,4-a]isoquinolines Containing Intramolecular Hydrogen Bonds - Alizadeh, Abdolali; Bayat, Fahimeh; Zhu, Zhe (Synlett, 2016)
A simple and efficient one-pot method is described for the construction of [1,4]thiazepino[5,4-a]isoquinolines containing intramolecular hydrogen bonds by a sequential four-component domino reaction of isoquinoline, a 2-bromoacetophenone, an aryl isothiocyanate, and dimethyl acetylenedicarboxylate.
Keywords: heterocycles; polycycles; isoquinolines; hydrogen bonds; domino reactions; multicomponent reactions